Association Study of MTHFR C677T Polymorphism With Homocysteine Level and Coronary Heart Disease in Elderly Patients - Li Chen; Yi Jiang (Cardiology Research and Practice)
Conclusion: MTHFR C677T mutation is significantly associated with the serum Hcy, and is an important genetic risk for CHD development in the elderly people living in the coastal area of eastern Zhejiang province, China.